2015
DOI: 10.1515/eces-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

The Use Of Mosses In Biomonitoring Of Selected Areas In Poland And Spitsbergen In The Years From 1975 To 2014

Abstract: Abstract:We have compared historical changes in concentrations of the heavy metals Mn, Ni, Cu, Zn, Cd and Pb accumulated in samples from the Polish woodlands of Beskidy and Karkonosze (S, SE Poland) and the north-east regions of the country, versus the relatively little polluted areas of Spitsbergen of the Svalbard Archipelago. We have combined the results from literature with new results from 2014. The regions of Beskidy and Karkonosze were the most exposed to heavy metals deposition. However, from 1975 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The concentrations of heavy metal were of the same magnitude (>10 µg/g) in both places [10,31,40]. Baret et al [68] showed the existence of a strong correlation between the blue shift and the severity of damage to vascular plants, mosses and lichens.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The concentrations of heavy metal were of the same magnitude (>10 µg/g) in both places [10,31,40]. Baret et al [68] showed the existence of a strong correlation between the blue shift and the severity of damage to vascular plants, mosses and lichens.…”
Section: Discussionmentioning
confidence: 91%
“…Other macro-, and microelements are at a similar level in the areas surrounding Longyearbyen and the natural areas of the Advent valley: 0.307 mg/g Mn, 0.050 mg/g Cu and 0.151 mg/g Zn. Although plant roots accumulate poisonous ions in cell walls, vacuoles and other places, this may not have a significant influence on plant physiology [31,69]. Salix polaris is characterized by the strong bioaccumulation of Zn, with concentrations of Cd and Pb at the detection level (0.0008 mg/g of Cd and 0.0044 mg/g Pb); as Cd and Pb are toxic heavy metals, the concentrations confirm that S. polaris isn't significantly affected by heavy metals in the concentration levels found here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrumental detection limits (IDL), the instrumental quantification limits (IQL) for the spectrometer iCE 3500, and the concentrations of heavy metals in certified reference materials BCR-414 plankton and BCR-482 lichen (Institute for Reference Materials and Measurements, Belgium) were previously presented in Kłos et al [24].…”
Section: Quality Controlmentioning
confidence: 99%
“…deposition of nitrogen, sulphur, and heavy metals) and habitat loss have been identified as major current threats for biodiversity [Millennium Ecosystem Assessment, 2005;Kłos et al, 2015]. Tundra ecosystems (alpine treeless) belong to the most valuable natural phenomena worldwide.…”
Section: Introductionmentioning
confidence: 99%